2014
DOI: 10.1016/j.jgeb.2014.08.001
|View full text |Cite
|
Sign up to set email alerts
|

FOXO 1a and FOXO 3a gene polymorphisms in association with metabolic syndrome

Abstract: The prevalence and magnitude of childhood and adult obesity and diabetes are increasing dramatically. FOXO 1a and FOXO 3a will be evaluated in this study, in an effort to identify genetic polymorphisms in potential candidate genes that may be associated with body mass index (BMI), and metabolic syndrome (MS). Also to assess whether there is a relation between insulin sensitivity, and genotype, we will test the relation between fasting insulin, glucose, insulin resistance, insulin secretion and genotype.A total… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2017
2017
2019
2019

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 14 publications
0
1
0
Order By: Relevance
“…Consistently, our team found that FoxO3 expression was elevated in the livers of rats fed a high-fat diet via microarray analysis and confirmed by real-time PCR (Additional file 1: Figure S1a). In human studies, there was a correlation between FoxO3 gene polymorphism and the insulin resistance index and body mass index [16]. Together, these results imply that abnormal expression of FoxO3 may be closely associated with NAFLD.…”
Section: Introductionmentioning
confidence: 94%
“…Consistently, our team found that FoxO3 expression was elevated in the livers of rats fed a high-fat diet via microarray analysis and confirmed by real-time PCR (Additional file 1: Figure S1a). In human studies, there was a correlation between FoxO3 gene polymorphism and the insulin resistance index and body mass index [16]. Together, these results imply that abnormal expression of FoxO3 may be closely associated with NAFLD.…”
Section: Introductionmentioning
confidence: 94%